2008
DOI: 10.1113/jphysiol.2008.152793
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional long‐term motor cortical plasticity and metaplasticity induced by quadripulse transcranial magnetic stimulation

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising tool to induce plastic changes that are thought in some cases to reflect N -methyl-d-aspartate-sensitive changes in synaptic efficacy. As in animal experiments, there is some evidence that the sign of rTMS-induced plasticity depends on the prior history of cortical activity, conforming to the Bienenstock-Cooper-Munro (BCM) theory. However, experiments exploring these plastic changes have only examined priming-induced effects on a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
255
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 251 publications
(280 citation statements)
references
References 61 publications
(111 reference statements)
23
255
1
1
Order By: Relevance
“…2c), whereas PAS still exerted significant effects on subsequent motor learning. This observation is in agreement with studies in rat hippocampus (Huang et al, 1992) and human motor cortex (Hamada et al, 2008) which demonstrated homeostatic metaplasticity even in the absence of altered synaptic excitability by the conditioning stimulation. Furthermore, this dissociation is consistent with the BCM model of bidirectional synaptic plasticity which proposes changes in the history of postsynaptic activity but not necessarily induction of synaptic plasticity as the determinant of homeostatic metaplasticity (Bienenstock et al, 1982).…”
Section: Methodssupporting
confidence: 81%
“…2c), whereas PAS still exerted significant effects on subsequent motor learning. This observation is in agreement with studies in rat hippocampus (Huang et al, 1992) and human motor cortex (Hamada et al, 2008) which demonstrated homeostatic metaplasticity even in the absence of altered synaptic excitability by the conditioning stimulation. Furthermore, this dissociation is consistent with the BCM model of bidirectional synaptic plasticity which proposes changes in the history of postsynaptic activity but not necessarily induction of synaptic plasticity as the determinant of homeostatic metaplasticity (Bienenstock et al, 1982).…”
Section: Methodssupporting
confidence: 81%
“…It was first examined in the visual system, where sensory experience could be altered and the subsequent effect on synaptic modification rules could be examined. Evidence for the sliding modification threshold was eventually obtained in multiple brain regions beyond the visual system [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We only performed the poststimulus evaluation at 30 min after the end of QPS. We chose this time point because the strong effect on the stimulated M1 was reported at this time window (Hamada et al 2008). We could not completely exclude the possibility that some changes may be induced in other parameters at different time points.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…This delivers a total of 360 trains, or 1,440 pulses. We chose these two parameters because QPS-5 is the most effective parameter for a long-term potentiation (LTP)-like effect over the stimulated M1, and QPS-50 is most effective for a long-term depression (LTD)-like effect over the stimulated M1 (Hamada et al 2008). …”
Section: Quadripulse Transcranial Magnetic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation